2021
DOI: 10.1002/adma.202103307
|View full text |Cite
|
Sign up to set email alerts
|

Pathologically Responsive Mitochondrial Gene Therapy in an Allotopic Expression‐Independent Manner Cures Leber's Hereditary Optic Neuropathy

Abstract: Leber's hereditary optic neuropathy (LHON) is a rare inherited blindness caused by mutations in the mitochondrial DNA (mtDNA). The disorder is untreatable and tricky, as the existing chemotherapeutic agent Idebenone alleviates symptoms rather than overcoming the underlying cause. Although some studies have made progress on allotopic expression for LHON, in situ mitochondrial gene therapy remains challenging, which may simplify delivery procedures to be a promising therapeutic for LHON. LHON becomes more diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 66 publications
1
9
0
Order By: Relevance
“…The results showed higher ROS in LHON fibroblasts compared to the control cells, indicating dysregulation of redox reactions ( Figure 5 C). The results were consistent with previous studies [ 29 , 30 , 31 ] and manifested the reliability of the data further.…”
Section: Resultssupporting
confidence: 93%
“…The results showed higher ROS in LHON fibroblasts compared to the control cells, indicating dysregulation of redox reactions ( Figure 5 C). The results were consistent with previous studies [ 29 , 30 , 31 ] and manifested the reliability of the data further.…”
Section: Resultssupporting
confidence: 93%
“…Even though the mitochondrial double membrane has proven to be a formidable barrier in targeting nucleic acids to the organelle, viruses, naked DNA, and RNA are observed to traverse the membranes 35 38 . To generate a mouse model carrying human mutated ND1 , we cloned the human ND1/m.3460G>A gene linked to a Myc epitope followed by a stop codon (without a tRNA) and mitochondrial encoded mCherry into a self-complementary AAV serotype 2 (AAV2) backbone (mut-hND1)( Fig 1A ), as described in the Materials and Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…GO/KEGG enrichment analysis indicated that the co-expressed genes of ECE2 were involved in mitochondrial expression, ATPase activity and cell cycle function. Some studies have found that the above-mentioned biological functions play an important role in the occurrence and development of tumors ( 27 29 ). These findings suggest that the co-expression network of ECE2 plays a key role in tumor initiation and progression.…”
Section: Discussionmentioning
confidence: 99%